DIPLOMASI PUBLIK PARIWISATA INDONESIA MELALUI NATION BRANDING 'WONDERFUL INDONESIA' DALAM MENINGKATKAN JUMLAH WISATAWAN JEPANG PERIODE 2021-2022 - Nadhila Harnifah (2023)
This research analyzes Indonesia's tourism public diplomacy efforts through nation branding 'Wonderful Indonesia' using the concepts of public diplomacy and nation branding. Qualitative research methods are used with a case study approach to public diplomacy in Japan. This research background is due to the phenomenon of a decrease in the number of Japanese tourists to Indonesia in recent years, even before the pandemic. Adaptation in the form of a derivative campaign from 'Wonderful Indonesia' along with supporting programs is a tool and medium for public diplomacy to attract foreign tourists. The results of the study show that the public diplomacy program implemented from 2021 to 2022 has succeeded in improving the image of Indonesian tourism in Japan and has implications for increasing Japanese tourist arrivals in Indonesia.